Excel 2010 introduction - Conway, Pamela; Safari eBooks ([S.l.] : CompuWorks, 2012)
"This class teaches the basic functions and features of Excel 2010. After an introduction to spreadsheet terminology and Excel's window components, you will learn how to use the Help system and navigate worksheets and workbooks. Next, you will enter and edit text, values, formulas, and pictures, and you will save workbooks in various formats. Additionally, you will move and copy data, learn about absolute and relative references, and work with ranges, rows, and columns. This course also covers simple functions, basic formatting techniques, managing large worksheets and printing."--Resource description page.
Presenter, Pam Conway.
Title from resource description page (viewed Apr. 12, 2013).
Keywords: Microsoft Excel (Computer file); Electronic spreadsheets; Electronic books